2022
DOI: 10.1096/fj.202200990rr
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the rhythmic diversity of daily photoreceptor outer segment phagocytosis in vivo

Abstract: Outer segment phagocytosis (OSP) is a highly‐regulated, biological process wherein photoreceptor outer segment (OS) tips are cyclically phagocytosed by the adjacent retinal pigment epithelium (RPE) cells. Often an overlooked retinal process, rhythmic OSP ensures the maintenance of healthy photoreceptors and vision. Daily, the photoreceptors renew OS at their base and the most distal, and likely oldest, OS tips, are phagocytosed by the RPE, preventing the accumulation of photo‐oxidative compounds by breaking do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…The cone OS tip phagocytosis/new OS synthesis cycle is thought to be approximately 12 h out of phase with that in rods in this diurnal process, with phagocytosis peaking in the early evening, approximately 4 h after the afternoon time point at 3:00 p.m., and new OS synthesis initiating thereafter. 36 Thus, as rod OS tip phagocytosis is peaking in the morning, new cone OS synthesis is ongoing. Notably, as opposed to the afternoon, we found that lactate was imported from the choroid circulation in the morning ( Figure 5F ).…”
Section: Resultsmentioning
confidence: 99%
“…The cone OS tip phagocytosis/new OS synthesis cycle is thought to be approximately 12 h out of phase with that in rods in this diurnal process, with phagocytosis peaking in the early evening, approximately 4 h after the afternoon time point at 3:00 p.m., and new OS synthesis initiating thereafter. 36 Thus, as rod OS tip phagocytosis is peaking in the morning, new cone OS synthesis is ongoing. Notably, as opposed to the afternoon, we found that lactate was imported from the choroid circulation in the morning ( Figure 5F ).…”
Section: Resultsmentioning
confidence: 99%